Corpora in cognitive linguistics : corpus-based approaches to syntax and lexis - Gries, Stefan Thomas, 1970-; Stefanowitsch, Anatol, 1970- (Trends in linguistics. Studies and monographs ;, 2006)
Cognitive Linguistics, the branch of linguistics that tries to "make one's account of human language accord with what is generally known about the mind and the brain," has become one of the most flourishing fields of contemporary linguistics. The chapters.